The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/mmr.2018.8516
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 inactivates hepatic stellate cells via downregulation of the TGF-β1/Notch signaling pathway

Abstract: Interleukin-22 (IL-22) inhibits liver fibrosis by inducing hepatic stellate cell (HSC) senescence, primarily through the activation of signal transducer and activator of transcription 3 signaling. However, whether other signaling pathways are involved remains unknown. The present study assessed the regulatory mechanism between IL‑22 and the Notch signaling pathway in vitro. The results revealed that IL‑22 had anti‑proliferative effects on HSC‑T6 cells, and cellular inactivation was reflected by simultaneous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…IL-22 can also activate signal transducer and activator of transcription 3 (STAT3) signaling in HSCs and induce their death by senescence, contributing to resolution of liver fibrosis [105]. At the same time, IL-22 was shown to inactivate HSCs by downregulation of the TGF-β1/Notch signaling pathway in HSCs [106].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…IL-22 can also activate signal transducer and activator of transcription 3 (STAT3) signaling in HSCs and induce their death by senescence, contributing to resolution of liver fibrosis [105]. At the same time, IL-22 was shown to inactivate HSCs by downregulation of the TGF-β1/Notch signaling pathway in HSCs [106].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…IL-17 seems to have dose-and cell source-dependent inflammatory and pro-fibrotic effect, whereas interleukin 22 (IL-22) was associated with protecting against liver fibrosis through downregulation of the TGF-b1/Notch signaling pathway [194] but being pro-fibrotic in cardiac fibrosis through STAT3/and ERK and IL-17, IL-6, IL-1b, IFN-g, and TNF-a [195] and pro-atherosclerotic [196]. Both, IL-17 and IL-22 are associated with poor prognosis in liver cancer [197], but the exact roles of IL-17 and IL-22 need to be defined in detail in regard to concentration, kind of inflammation, and period of chronic inflammation involved in signaling axis and cell sources.…”
Section: Disruption Of Gut Bacteria Composition As Internal Pathogenimentioning
confidence: 99%
“…TGFβ superfamily ligands bind to the type II receptor and recruit the phosphorylated type I receptor, which then phosphorylates receptor-regulated SMADs, finally forming a complex that accumulates in the nucleus. These ligands then act as transcription factors and participate in the regulation of the expression of target genes, including α-SMA, collagen I and FN (24). In the present study, it was first observed that overexpression of HOXA11-AS upregulated the mRNA and protein levels of TGFβ1, whereas knockdown of HOXA11-AS decreased these levels.…”
Section: Discussionmentioning
confidence: 47%